Tolerance towards wildlife in the Atlantic forest: an empirical test across ecological contexts and mammal specie - Teixeira, Lucas Manuel Cabral (2018)
Human-wildlife conflicts (HWC) emerge as complex conservation challenges impairing human livelihood and wildlife populations. Research on HWC, however, has traditionally approached these components apart and focused on single/ similar species, hampering a broader understanding of the connections between ecological drivers and human dimensions of conflicts. We here develop and test a model integrating ecological and human components of HWC, focusing on three species - opossum, crab-eating fox and puma. We investigated the pathways through which the ecological context (forest cover) affects experiences with wildlife (contact and damage), and how such experiences influence tolerance via beliefs, emotions and attitude. We interviewed 114 landowners across 13 landscapes varying in forest cover in a region of the Brazilian Atlantic forest and tested our model using Piecewise Structural Equation Modeling. We found that: i. forest cover negatively affected tolerance, but just towards the largest species; ii. relevance and effects of distinct experiences with wildlife on beliefs and emotions varied across species; iii. beliefs and emotions influenced tolerance, but negative emotions were relevant only for the largest species. Conflicts with larger species can then be understood as disservices provided by forests, indicating the relevance of framing HWC within a broader perspective that consider the trade-offs with ecosystems services. For some species, positive experiences with wildlife may counteract the negative effects of damages to livestock in shaping human behavior. Models such as ours - that structure relationships between ecological and human components - can help identifying deeper, more effective leverage points to improve interventions to mitigate HWC